The Effect of High-Performance Concrete on the Strength and Durability of Double Tee Beams - Sally Selan Hussein; Hussam Ali Mohammed; Ali Mohammed, Ayad (International Journal of Integrated Engineering, 2025)
This paper presented an experimental and analytical investigation of the behavior of a double tee beam under the influence of flexure by using High-performance concrete. double tee beams can play an effective role in the span challenges in structural engineering by making a balance between material strength, geometric design, and load-carrying capacity. Three beams were tested experimentally with f’c equal to 30 MPa for the first beam and 40 MPa for the other two beams by making a model according to the available capabilities and testing it up to failure, the first beam was subjected to normal external conditions, and the other one was subjected to the effect of MgSO4 salt for six months. The result of the test show that high-performance concrete can save the strength of concrete as possible and protect the beam from corrosion. The difference ratio between the two tested beams equals 4.47%. Increasing the amount of compressive strength which is obtained as a result of using High-performance concrete had an effect in reducing the amount of stresses that occurred, thus reducing cracks and controlling their expansion. The beams were analyzed theoretically by using a powerful program (ABAQUS 2019) using the same mechanism of loading, same compressive strength, and material properties. The behavior of the beams is similar to their behavior from the experimental test with a difference ratio equal to (2.67% and 2.89%) for Double Tee Beam with the symbol DTB1 and DTB2, respectively.